Photocatalytic CO2 reduction to syngas using metallosalen covalent organic frameworks - Wei Zhou; Xiao Wang; Wenling Zhao; Naijia Lu; Die Cong; Zhen Li; Peigeng Han; Guoqing Ren; Lei Sun; Chengcheng Liu; Wei-Qiao Deng (Nature Communications, 2023)
Abstract Metallosalen-covalent organic frameworks have recently gained attention in photocatalysis. However, their use in CO2 photoreduction is yet to be reported. Moreover, facile preparation of metallosalen-covalent organic frameworks with good crystallinity remains considerably challenging. Herein, we report a series of metallosalen-covalent organic frameworks produced via a one-step synthesis strategy that does not require vacuum evacuation. Metallosalen-covalent organic frameworks possessing controllable coordination environments of mononuclear and binuclear metal sites are obtained and act as photocatalysts for tunable syngas production from CO2. Metallosalen-covalent organic frameworks obtained via one-step synthesis exhibit higher crystallinity and catalytic activities than those obtained from two-step synthesis. The optimal framework material containing cobalt and triazine achieves a syngas production rate of 19.7 mmol g−1 h−1 (11:8 H2/CO), outperforming previously reported porous crystalline materials. This study provides a facile strategy for producing metallosalen-covalent organic frameworks of high quality and can accelerate their exploration in various applications.